Minimally Invasive Treatment of Patients with Acute Appendicitis - Alexei L. Charyshkin; Maksim M. Yartsev; Oleg V. Midlenko; Antonina V. Smolkina; Nikolai I. Belonogov (International Journal of Biomedicine, 2019)
The aim of our study was to improve the surgical treatment of patients with acute appendicitis (AA) by improving the mini-incision approach. Materials and Methods: The study included 220 patients (mean age of 38.9±14.3 years) with AA, who underwent surgical treatment in the period from 2008 to 2017. A mini-incision appendectomy was performed on all patients. Patients were divided into 2 groups. The groups were comparable with respect to age and sex. Group 1 included 140 patients who underwent appendectomy by the traditional method of minilaparotomy with the classical sanitation and drainage of the abdominal cavity. Group 2 included 80 patients who underwent appendectomy by the developed method of a minimally invasive approach and sanitation and drainage of the abdominal cavity. Results: The developed method of minilaparotomy expands and improves the area of accessibility by an average of 4.8cm2 for surgical manipulations during an appendectomy. The proposed method of minilaparotomy reduces the duration of an appendectomy by an average of 11.5 minutes, and the rate of complications during surgery and purulent-inflammatory complications by 3.9%.